Performance and mechanism of Congo red degradation by Fe-Cu bimetallic MOFs in Fenton-like system - GONG Jiankang; ZHOU Qingyun; QU Yanmei; CHEN Ni; WANG Yaqiu; WANG Bangyan (Cailiao gongcheng)
To solve the problems in Fenton-like reactions， such as slow Fe3+/Fe2+ redox cycle， low electron transfer rate at the material interface， and high electron density of Fe3+ in Fe-MOFs， Fe-Cu bimetallic nitro-functionalized MOFs material （NMIL-88B-Cu-1） is synthesized by a one-step solvothermal method based on the principle of redox coupling reaction. The material is characterized and applied to effectively degrade Congo red （CR） in a Fenton-like process. The effects of different materials， H2O2 dosage， pH， CR concentration， and coexisting ions on the degradation of CR are investigated. The stability of materials is verified， and the catalytic degradation mechanism is proposed. The results show that when the molar percentage of Fe3+ and Cu2+ are both 50%， NMIL-88B-Cu-1 with hexagonal rod structure and mesoporous can be assembled on α-Fe2O3. When CR is 10 mg/L， pH value is 3-7， NMIL-88B-Cu-1 catalyst is 0.1 g/L， and H2O2 is 0.5 mol/L， CR can be rapidly and efficiently degraded in 15 min. The degradation efficiency of CR is 98%， which is 1.95 times that of NO2-MIL-88B and 2.24 times that of MIL-88B， respectively. The CR degradation efficiency could still reach 92% after 4 cycles， the content ratio of Fe3+/Fe2+ is only reduced by 5%， and its crystal structure remains the same， exhibiting the high cycle stability of NMIL-88B-Cu-1. In the system SO42- and NO3- do not affect the degradation of CR， while Cl- and H2PO4- with a concentration of 0.09 mo/L show an inhibitory effect on the degradation of CR. The analysis of the mechanism shows that the electron density of Fe3+ in the center of the nitro-functionalized material is low， and the introduction of Cu2+ constructs Fe-Cu bimetallic MOFs materials. The redox coupling reaction between Fe and Cu and the synergistic effect of Fe-Cu promote the formation of Fe2+ effectively， and accelerate the e- transfer at the interface of NMIL-88B. The generated ·OH can oxidize and degrade CR into inorganic small molecules such as CO2 and H2O.